2011
DOI: 10.1029/2011gl049423
|View full text |Cite
|
Sign up to set email alerts
|

Glaciation temperatures of convective clouds ingesting desert dust, air pollution and smoke from forest fires

Abstract: [1] Heavy aerosol loads have been observed to suppress warm rain by reducing cloud drop size and slowing drop coalescence. The ice forming nuclei (IFN) activity of the same aerosols glaciate the clouds and create ice precipitation instead of the suppressed warm rain. Satellite observations show that desert dust and heavy air pollution over East Asia have similar ability to glaciate the tops of growing convective clouds at glaciation temperature of Tg < ∼ −20°C, whereas similarly heavy smoke from forest fires i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
95
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 83 publications
(105 citation statements)
references
References 24 publications
9
95
0
1
Order By: Relevance
“…A recent observational study corroborated that increasing CCN decreases the cloud glaciation temperature and thus increases the abundance of the mixed-phase regime (Zipori et al, 2015). With abundant INPs such as dust particles, clouds glaciate at a much warmer temperature (Rosenfeld et al, 2011;Zipori et al, 2015). It was found that commonly occurring supercooled water in the clouds near the coastal regions of the western US is associated with low-CCN and limited-INP conditions .…”
Section: Introductionmentioning
confidence: 52%
“…A recent observational study corroborated that increasing CCN decreases the cloud glaciation temperature and thus increases the abundance of the mixed-phase regime (Zipori et al, 2015). With abundant INPs such as dust particles, clouds glaciate at a much warmer temperature (Rosenfeld et al, 2011;Zipori et al, 2015). It was found that commonly occurring supercooled water in the clouds near the coastal regions of the western US is associated with low-CCN and limited-INP conditions .…”
Section: Introductionmentioning
confidence: 52%
“…As glaciation often occurs at warmer temperatures, we perform a sensitivity simulation to this temperature cutoff, described below. We justify this temperature threshold since super-cooled liquid clouds can exist at temperatures as cold as 238 K, although the onset of glaciation can occur at temperatures as warm as 258-263 K (Rosenfeld and Woodley, 2000;Rosenfeld et al, 2011). Recent studies indicate that low-level liquid clouds are ubiquitous in all seasons in remote regions such as the Arctic (e.g., Cesana et al, 2012).…”
Section: Brownian Coagulation Between Interstitial Particles With Clomentioning
confidence: 99%
“…3). Nominally, only one in a million particles can act as an INP at -20°C (39)(40)(41)(42)(43)(44)(45). If the temperature is reduced sufficiently, then all CCN can potentially act as sites for ice to form on by homogeneous freezing.…”
Section: Ice and Mixed-phase Cloudsmentioning
confidence: 99%